A review of hydrology, sediment and water resource use in the Blue Nile Basin - Awulachew, Seleshi Bekele; McCartney, Matthew P.; Steenhuis, Tammo S.; Ahmed, A.A. (International Water Management Institute, 2008)
This working paper has been prepared as one of the outputs of the 'Improved water and land management in the Ethiopian Highlands and its impact on downstream stakeholders dependent on the Blue Nile' project, supported by the CGIAR Challenge Program on Water and Food (CPWF). It provides a comprehensive literature review; identifies types, sources and provides geo-referencing of data in the basin; compiles information of hydrology, sediment, and water resources and its uses. It also provides a review of applicable models for watershed and water allocation simulation, research methods, past studies and published material related to the Blue Nile. Extensive reference material and previous studies are compiled.